EVALUATION OF ANTIDIABETIC ACTIVITY OF LYOPHILIZED TOMATO AND LEMON JUICES ALONE AND IN COMBINATIONEVALUATION OF ANTIDIABETIC ACTIVITY OF LYOPHILIZED TOMATO AND LEMON JUICES ALONE AND IN COMBINATION - Anum Naseer Bhatti; Muhammad Ovais Omer; Muhammad Adil Rasheed; Shaista Qamar (Journal of Animal and Plant Sciences, 2026)
The present study aimed to compare the impact of lyophilization on the phytochemicals and in-vitro antidiabetic activity of tomato and lemon fruit juices alone and in combination, and compares their efficacy with fresh samples by using different analytical techniques. For the phytochemical analysis of samples, conventional methods like Gas Chromatography Mass Spectrometry (GC-MS), Fourier Transformed Infrared Spectroscopy (FTIR) and High-Performance Liquid Chromatography (HPLC) were used. HPLC technique was used to confirm flavonoid compounds i.e. quercetin, myricetin and kaempferol in isopropyl alcohol, methanol and acetonitrile extracts. Furthermore, in vitro antidiabetic activity was determined by using inhibition of alpha amylase enzyme and glucose uptake by yeast cells assays. Both lyophilized juices of lemon and tomato demonstrated high phenolic and flavonoid content than fresh samples. Lemon demonstrated higher total phenolic content of 7.15 mg/g, while tomato contained higher total flavonoid content of 73.75 mg/g, both of which are important to play critical role in glucose metabolism and antioxidant defense. When compared with fresh juices results, the lyophilized samples exhibited comparable phytochemical stability and biological activity, highlighting the effectiveness of lyophilization in preserving bioactive compounds. On the other hand, the combination extract (IC50 = 7.76 mg/ml) of lemon and tomato showed significant inhibition of alpha amylase enzyme activity in a concentration dependent manner (P<0.05) and enhanced glucose uptake in yeast cells, suggesting a complementary effect in all glucose concentration of 5, 10 and 25 mM. These findings indicate that both lemon and tomato contribute beneficially to antidiabetic activity, particularly when used in combination. Future studies should focus on validating these findings by using in-vivo models and exploring formulation strategies for diabetes management. Overall, this research also adds novelty of employing lyophilization as a successful preservation technique, thus offering a potential natural remedy for diabetes.
Keywords: α-Amylase; Flavonoids; Glucose uptake; Lemon; Antidiabetic; Tomato